Pendampingan Penyusunan Strategi Keberlanjutan Usaha Start-up Siklus Refill Indonesia Melalui Pengelolaan Green Products - Yelita Anggiane Iskandar; Adji Candra Kurniawan; Mirna Lusiani; Rahmad Inca Liperda; Nur Layli Rachmawati; Silvia Dian Anggraeni; Frieska Haridha; Wegik Dwi Prasetyo; Ika Dyah Widharyanti; Laksamana Sakti (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
The linear economic system that has been applied in the industrial world poses various risks, one of which can be seen in the increase in the consumption of industrial products. An alternative to the traditional linear economy concept is called a circular economy, which in principle aims to reduce consumption waste by optimizing existing resources. The biggest challenge in implementing a circular economy is the need to shift people's ingrained behavior through the linear economic system. The challenges of implementing a circular economy can be slowly addressed in various ways, one of which is by providing environmental awareness education to the public that raises the importance of switching to green products. The start-up company “Siklus Refill Indonesia” utilizes innovation and digital technology related to the marketing of daily necessities products to end consumers. The business model offered is intended to deal with the problem of plastic waste from the source by replacing the use of sachet packaging by distributing daily goods directly to consumers with a last-mile delivery system, so that consumers can use their containers, and contribute significantly to the preservation of the earth.